PERANCANGAN ALAT PENGUPAS SABUT KELAPA MENGGUNAKAN METODE VDI 2221 - Prima, Febri; Japri, Bryan Anthony; Kurniawan, Eddy; Lubis, Gita Suryani; Ivanto, Muhammad; Ivontianti, Wivina Diah; Oktaviani, Eva Pramuni (Teknik Industri Unikom, 2021)
The increasing demand for coconut productin in Sungai Kupah Village, Kuburaya Regency has resulted in workers needing a tool that can complete work more quickly and effiently. The tools used today stil use wedges where their use takes a long tie because the process in the process relies on human power. In additin, with non-ergonomic work positins, workers can also experience several work-related diseases such as back pain and back pain. The objecties of this research are (1) Designing an ergonomic coconut peeler according to consumer needs (2) Testig the performance of the tool (3) Testig worker fatiue before and aftr using the tool (4) Testig the level of consumer satifactin. The solutin used in this study is the VDI 2221, CVL method approach, measuring tool performance and analyzing the level of satifactin. The results obtained in this study are (1) produce a tool design according to consumer needs and have paid attntin to ergonomic aspects (2) The design of this tool produces a fairly fast stripping tie of 143 peeling fruit/hour when compared to tools using a wedge, namely 92 peeling fruit/hour (3) Worker fatiue test aftr using this tool showed 14.42 % of coconut owners, 11.20 % of worker 1 and 10.48 % of worker 2. This test resulted in CVL below 30% where workers did not experience fatiue. (4) Respondents feel comfortable with the designed tool as evidenced by the results of the 4.8 Linkert scale. Meanwhile, for ease of operatin, the result is 4.3, which means that respondents fid it easy to operate the designed tool. The conclusion in this study is that the currently designed tools are quite effctie, ergonomic and able to reduce the level of worker fatiue.